1976
DOI: 10.1099/00221287-92-1-120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medium Redox Potential on the Folate-limited Growth of Lactobacillus casei var. rhamnosus

Abstract: SUMMARYThe medium redox potential (Eh) influenced the folate-limited growth of Lactobaci1h.s casei; the growth response was maximal at an Eh of +12omV (pH6-35). At raised Eh serum folate would support less growth than pteroylghhunic acid, and the response to N6-methyl tetrahydrofolic acid was intermediate between them. Pteroylglutamic acid was not destroyed during 24h incubation at 37 "C in medium with values between +40 and +~o mV. Destruction of N5-methyl tetrahydrofolic acid occurred within 24h when the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A complete 2 3 factorial design was used to study the main e¡ects and interactions of Eh, NaCl and AA on L. plantarum. The two-level experimental range (31 and 1) for each factor is detailed in Table 1.…”
Section: Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete 2 3 factorial design was used to study the main e¡ects and interactions of Eh, NaCl and AA on L. plantarum. The two-level experimental range (31 and 1) for each factor is detailed in Table 1.…”
Section: Equationmentioning
confidence: 99%
“…Di¡er-ent studies have shown that LAB have the capacity to reduce their environmental Eh [1,2], and have an optimum medium Eh for growth [3], but whereas a highly oxidant Eh has been shown to be an inhibiting factor for these bacteria [4], there is little information available on the in£uence on LAB of a reducing Eh. There is an industrial interest to understand the consequences of the reduction activity of LAB on their own physiology during lactic acid fermentation [5], and also to study the potential use of reducing Eh to better control the contamination of foods by these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…mesenteroides leading to acidification and decrease in oxidoreduction potential ( E h7 ) from +200 to −240 mV (Van Dijk et al 2000). Previous studies have shown the reductive capacity of another LAB, Lactococcus cremoris (Keen 1972) and the existence of an optimum medium redox potential for Lactobacillus casei growth (Tennant 1976). In yogurt fermentation, the incubation time that was needed to reach pH 4·5 was increased by 6 h by the addition of cysteine (500 mg l −1 , −217 mV) compared with standard conditions (−70 mV) (Dave and Shah 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One such factor is oxidoreduction potential (Eh). Different studies have shown that LAB have the capacity to reduce their environmental Eh [1,2], and have an optimum medium Eh for growth[3], but whereas a highly oxidant Eh has been shown to be an inhibiting factor for these bacteria[4], there is little information available on the influence on LAB of a reducing Eh. There is an industrial interest to understand the consequences of the reduction activity of LAB on their own physiology during lactic acid fermentation[5], and also to study the potential use of reducing Eh to better control the contamination of foods by these microorganisms.…”
Section: Introductionmentioning
confidence: 99%